Sustainable energy and archaeology (AmS-Skrifter, 2026)
The number of linear projects such as transmission lines, pipelines, and roads and cables within solar parks increases rapidly due to changing needs for sustainable energy and energy infrastructure. While the supervision of trenches is undoubtedly valuable, this type of archaeology also holds certain restraints, and the results are not necessarily comparable to systematically excavated sites. According to the current recommendations of the Danish Agency of Culture and Palaces, the solar parks need not be systematically examined, but it is argued here, that they pose an immanent threat to our cultural landscapes. Due to the increasing number of such projects, it is becoming increasingly urgent to address certain methodological problems and to increase the awareness of potential threats to the archaeological remains.